0007 Simulation based medical education as a student selected component for medical students. (2nd November 2015) - Fent, Graham; Gopal, Alan; Purva, Makani
Abstract : Background: In spite of the wealth of research and guidance devoted to acquisition of skills and competencies at undergraduate level, no formal training programme exists to train medical students to use simulation-based medical education (SBME) as a teaching tool to assess the viability of introducing medical students to using SBME themselves as future medical educators. Theoretical benefits of doing so include the fact that healthcare professionals spend a great deal of their working lives as educators 1 and, through understanding the processes involved in teaching SBME, students will themselves become better learners. Description: Our centre ran a three-week medical student selected component (SSC) aimed at teaching the principles of and practical skills required to provide effective SBME. The programme included training on operating high-fidelity mannequins, debriefing in SBME, procedural skills and emergency scenarios. Students were able to attend in-situ simulation exercises and human factors training. By the end of the SSC, they were fully independent in designing and conducting an emergency scenario and providing basic structured debriefing on this. On-going reflection through the course was encouraged, with an emphasis on students understanding their own non-technical skills and behaviours and how these improved through the SSC. Outcomes: Feedback obtained from the course suggested this programme is a viable means of introducing medical students to the main concepts of SBME to use in their capacity as future medical educators. Students found the course enjoyable and felt it had met their learning objectives. It is hoped that that this report will encourage further adoption of this exciting initiative in medical and other healthcare undergraduate courses. Take home messages: Teaching medical students about the process of using SBME as future educators could help with increased uptake and use of SBME Teaching SBME as an SSC is viable and well received by students Reference: Dandavino M, Snell L, Wiseman J. Why medical students should learn how to teach. Med Teach 2007;29:558–565